Enterprise Management Decision and Financial Management Based on Dynamic Cost Volume Profit Model. (23rd June 2022) - Guo, Yanlin
Abstract : Under the background of today's times, the internal and external environment of enterprises is complex and changeable. It is of great significance for the survival and development of enterprises to continuously reduce the business risks and improve the economic benefits of enterprises by adopting scientific decision-making methods. CVP (cost volume profit) analysis is a model established by sorting out variables related to business decisions in enterprise production through mathematical modeling. Based on the interpretation of cost behavior by multiple cost drivers, this paper establishes a dynamic CVP model of traditional CVP analysis, breaks through the limitations of original assumptions, and improves the application value of CVP analysis in practice. The model is applied to the business decision-making and financial management of a case enterprise, and the products with different characteristics of the enterprise are modeled and analyzed, so as to provide targeted improvement suggestions or strategies for the enterprise's product production decision-making. The research shows that the dynamic CVP model can be used to formulate the financial management strategy to optimize the profits of enterprises, and it can achieve stable profits and development in the market competition.